XPS detection of unusual Cu(II) to Cu(I) transition on the surface of complexes with redox-active ligands - Ivanova, T.M.; Maslakov, K.I.; Sidorov, A.A.; Kiskin, M.A.; Linko, R.V.; Savilov, S.V.; Lunin, V.V.; Eremenko, I.L. (Journal of electron spectroscopy and related phenomena, 2020)
•We observed valence tautomerism in copper complex.•Antiferromagnetic spin interaction at low temperature was assumed.•The role of ligands was revealed. Electronic structure of copper complexes with redox-active ligands was studied by XPS. The temperature dependence of the redistribution of electron and spin densities was shown. A low temperature anomaly of magnetic properties of the copper complex with redox-active ligands was detected. The observed two states of copper (Cu+1 and Cu+2) allowed proposing valence tautomerism («redox-isomer» copper complex). The donating role of nitrogen atoms was established in the copper complex with redox-active ligand. The role of ligands in the formation of the electronic structure of square-planar complexes was revealed.